UM ESTUDO COM ESTUDANTES DE PEDAGOGIA ACERCA DO ZOOLÓGICO COMO ESPAÇO DE APRENDIZAGEM EM CIÊNCIAS: ENFOQUE NOS OFÍDIOS - Lima, Kelly Regina Linzmeier de (2023)
This is a research on non-formal education spaces allied to formal spaces, which has the potential to contribute to the science learning process. The space used was the zoo in the municipality of Cascavel, Paraná, these spaces generally have an organized structure for public visitation, which allows the observer to contemplate the diversity of fauna and flora, in different aspects. The main focus was the serpentarium. The objective was to analyze the contributions of a proposal for pedagogical workshops in science teaching in non-formal learning environments. The qualitative approach research, through content analysis, mediated through meaningful learning, proposed by David Ausubel, in this way, questionnaires were used before and after the workshops, to measure what the participants knew, and (post) workshop it was to find out how much they expanded their cognitive network. There were 16 participants, academics from the pedagogy course at a private college in the municipality of Cascavel, who participated in all the workshops and the guided tour, providing entry into restricted areas, such as the snake management area. The survey results showed that about 50% understood the social function, knowing how to inform and publicize how the animals arrive at the zoo, through smuggling, mistreatment and not through the capture carried out only for the animal's exhibition. 94% of them learned the correct nomenclature, between snakes and serpents. It can be said that there was a noticeable expansion of the concepts discussed. It is expected that future teachers' self-confidence in teaching outside the classroom will be strengthened, making it possible to understand that the workshops allow the reconfiguration of previously established knowledge.